Toughness and Structural Analysis of Welds and HAZ of Sumerged Arc Welding on SM 490 Steel - Sianipar, Stiven Ewin; hasibuan, fardin; Syaputra, Muhammad Lyan (Universitas Riau Kepulauan, 2025)
The welding process is a metal joining method that utilizes high heat energy, which can trigger changes in the microstructure, deformation, and the emergence of residual stress in the area around the joint. This study aims to examine the impact of variations in heat input in the Submerged Arc Welding (SAW) process on the microstructure and toughness of SM 490 steel, especially in the weld area and heat-affected zone (HAZ). The SAW method was chosen because it has high efficiency, is easy to automate, and is able to produce good quality joints. This study used three levels of heat input, namely 2.1 kJ/mm, 3.16 kJ/mm, and 4.3 kJ/mm. Based on the test results, increasing heat input causes slower cooling, which affects the formation of microstructures such as ferrite at the grain boundary, acicular ferrite, Widmanstätten ferrite, bainite, and martensite. Acicular ferrite with fine size and interlocking pattern is known to contribute to increasing the toughness of welded joints. The maximum toughness in the weld zone, amounting to 117 Joules, was achieved at a heat input of 3.16 kJ/mm with a test temperature of 0°C. Meanwhile, the best toughness value in the HAZ of 17.5 Joules was recorded at a heat input of 2.1 kJ/mm at a temperature of -20°C. The results of this study confirm that appropriate heat input settings are very important to obtain optimal microstructure and toughness in welding SM 490 steel using the SAW method